ANALISIS PENGARUH AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH TERHADAP KINERJA PEMERINTAH DAERAH - Auditya, Lucy; Husaini, Husaini; Lismawati, Lismawati (JURNAL FAIRNESS, 2013)
This study aims to prove the influence of accountability and transparency in the financial management of the performance of the local government area of the province of Bengkulu. This study used a questionnaire to collect the data, the sampling method used in this research is purposive sampling with sample criteria, namely Echelon III and Echelon IV, section Accounting or Section Bookkeeping on each Unit (SKPD) in the government of Bengkulu province. The results showed that the accountability of financial management and significant positive effect on the performance of the local government of Bengkulu province. This means that the higher accountability in financial management will be able to improve the performance of the local government of Bengkulu province. Similarly, the transparency of financial management, positive and significant effect on the performance of local government. In this case, the higher level of transparency in the financial management of local government performance will also be better. By increasing accountability and transparency in the financial management of all existing units expected to improve the performance of local governments in order to promote the establishment of good governance.